Otimização de Risers de materiais compósitos - Silva, Rafael Fernandes da (2012)
The depletion of oil and gas reserves has increasingly led to the search of deepwater fields. Most of recent oil and gas discoveries in Brazil occurred in deepwater fields. However, using steel risers for deepwater application is not always feasible, due to its high weight. In such enviroments, the traditional extraction and production risers made of steel tend to become expensive, due to increased top tension which overburdens the plataform. Fiber reinforced composite materials, being lighter, present interesting characteristics for offshore applications, such as high specific strength and stiffness, high corrosion resistance, good thermal insulation, high structural damping properties, and fatigue resistance. Thus, the application of composite risers is an interesting alternative to deepwater oil fields. The design of laminated composite risers is very difficult since the strength and stiffness of these components depend on the number of layers and the material, thickness, and orientation of each layer. Thus, the use of the conventional trial-and-error strategy is not adequate and it is necessary to apply optimization techniques. In this work, optimization techniques are applied to optimize composite catenary risers. the design variables are the thickness, the orientation and material of each layer. A multi-objective formulation is adopted to minimize the weight, cost and maximize the buckling safety factor of the composite riser. The optimization model includes strength and stability constraints and considers multiple load cases. The global analysis of the riser is carried out using the catenary equations and the stress computation in the critical locations is performed using the Classical Lamination Theory (CLT) and the theory of thin-walled tubes. It is important to note that, due to manufacture constraints, the design variables can only assume discrete values. Therefore, a genetic algorithm is used for optimization since it can easily handle discrete variables. In addition to classical genetic operators, as crossover and mutation, this algorithm also includes operators specially designed to handle laminate structures, such as layer swap and layer deletion. The proposed formulation is applied in the design optimization of composite catenary risers with different water depths and top angles. Numerical examples show that the proposed methodology is very robust